Problems with the performance of evidence in virtual audiences - Gonzales Ormachea, Ruben (2021)
In a pandemic, the hearings, in most cases, have been held virtually. However, although there have been good results, it is not an obstacle to wonder if these can be carried out with the same effectiveness as a face-to-face session. In this sense, we have considered analyzing the comparative and national legislation on the hearing of evidence. Next, we have identified the problems with the virtual test audience; specifically, we have focused on the psychology of testimony and how its development can be influenced by virtuality. Finally, we have suggested proposals to improve the service of our administration of justice.